PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF ADVENTURE IN LAKE TOBA BOARDGAME (ALTOBO) PADA SISWA KELAS V SDN 060874 MEDAN PERJUANGAN - Nur Afniasty Siregar; Fahrur Rozi; Nurmayani; Laurensia Masri Perangin-angin; Imelda Free Unita Manurung (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to develop an interactive learning media called Adventure in Lake Toba Boardgame (Altobo) that is valid, practical, and effective for teaching the IPAS topic Harmony in Ecosystems, which is adapted to the ecosystem of Lake Toba, for fifth-grade students at SDN 060874 Medan Perjuangan. This study employed a Research ang Development (R&D) approach using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The data collection techniques included questionnaires, observations, documentation, and interviews. The subjects of this study were 20 students of class V-A at SDN 060874 Medan Perjuangan. The results showed that the Altobo learning media obtained a material expert validation score of 88% and a media expert validation score of 95%, both categorized as highly valid. The practicality test yielded a score of 88%, indicating that the media was highly practical. Furthermore, the effectiveness test resulted in a percentage of 84,38%, categorized as highly effective, based on observations of students’ engagement during the learning process. Based on these findings, it can be concluded that this research and development study successfully produced the Adventure in Lake Toba Boardgame (Altobo), an interactive learning media that is valid, practical, and effective for use in elementary school IPAS learning.